PKHD1L1 is a coat protein of hair-cell stereocilia and is required for normal hearing - Xudong Wu (Nature Portfolio, 2019)
There is little known about the function or molecular identity of the electron-dense stereocilia coat, which is transiently present at the surface of stereocilia. In this study authors screened a database of hair-cell-enriched translated proteins to identify the expression of Polycystic Kidney and Hepatic Disease 1-Like 1 (PKHD1L1), a large, mostly extracellular protein, and show that it forms the coat at the tips of stereocilia and is required for normal hearing in mice